Advance care planning uptake among patients with severe lung disease: A randomised patient preference trial of a nurse-led, facilitated advance care planning intervention - Sinclair, C.; Auret, K.; Evans, S.; Williamson, F.; Dormer, S.; Wilkinson, A.; Greeve, K.; Koay, A.; Price, D.; Brims, Fraser (BM J Group, 2017)
Objective Advance care planning (ACP) clarifies goals for future care if a patient becomes unable to communicate their own preferences. However, ACP uptake is low, with discussions often occurring late. This study assessed whether a systematic nurse-led ACP intervention increases ACP in patients with advanced respiratory disease. Design A multicentre open-label randomised controlled trial with preference arm. Setting Metropolitan teaching hospital and a rural healthcare network. Participants 149 participants with respiratory malignancy, chronic obstructive pulmonary disease or interstitial lung disease. Intervention Nurse facilitators offered facilitated ACP discussions, prompted further discussions with doctors and loved ones, and assisted participants to appoint a substitute medical decision-maker (SDM) and complete an advance directive (AD). Outcome measures The primary measure was formal (AD or SDM) or informal (discussion with doctor) ACP uptake assessed by self-report (6 months) and medical notes audit. Secondary measures were the factors predicting baseline readiness to undertake ACP, and factors predicting postintervention ACP uptake in the intervention arm. Results At 6 months, formal ACP uptake was significantly higher (p<0.001) in the intervention arm (54/106, 51%), compared with usual care (6/43, 14%). ACP discussions with doctors were also significantly higher (p<0.005) in the intervention arm (76/106, 72%) compared with usual care (20/43, 47%). Those with a strong preference for the intervention were more likely to complete formal ACP documents than those randomly allocated. Increased symptom burden and preference for the intervention predicted later ACP uptake. Social support was positively associated with ACP discussion with loved ones, but negatively associated with discussion with doctors. Conclusions Nurse-led facilitated ACP is acceptable to patients with advanced respiratory disease and effective in increasing ACP discussions and completion of formal documents. Awareness of symptom burden, readiness to engage in ACP and relevant psychosocial factors may facilitate effective tailoring of ACP interventions and achieve greater uptake. Trial registration number ACTRN12614000255684. © Published by the BMJ Publishing Group Limited